Comprehending the evolution of gene editing platforms for crop trait improvement - Dhakate, Priyanka; Sehgal, Deepmala; Vaishnavi, Samantha; Chandra, Atika; Singh, Apekshita; Raina, Soom Nath; Rajpal, Vijay Rani (Frontiers in Genetics, 2022)
Abstract CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats)/Cas (CRISPR-associated) system, was initially discovered as an underlying mechanism for conferring adaptive immunity to bacteria and archaea against viruses. Over the past decade, this has been repurposed as a genome-editing tool. Numerous gene editing-based crop improvement technologies involving CRISPR/Cas platforms individually or in combination with next-generation sequencing methods have been developed that have revolutionized plant genome editing methodologies. Initially, CRISPR/Cas nucleasesreplaced the earlier used sequence-specific nucleases (SSNs) such as Zinc-finger nucleases (ZFNs) and Transcription activator-like effector nucleases (TALENs), to address the problem of associated off-targets. The adaptation of this platform led to the development of concepts such as epigenome editing, base editing and prime editing. Epigenome editing employed epi-effectors to manipulate chromatin structure. However, base editing uses base editors to engineer precise changes for trait improvement. Newer technologies like prime editing have now been developed as a “search-and-replace” tool to engineer all possible single-base changes. Owing to these platforms, the field of genome editing has evolved rapidly to develop crop plants with improved traits. In this review, we present the evolution of the CRISPR/Cas system into new-age methods of genome engineering across various plant species and the impact that they have had on tweaking plant genomes and associated outcomes on crop improvement initiatives.